On the catalytic hydrogenation of graphite for graphene nanoribbon fabrication - Schäffel, F; Warner, J; Bachmatiuk, A; Rellinghaus, B; Büchner, B; Schultz, L; Rümmeli, M (2009)
Recent research into the channelling of few layer graphene via catalytic hydrogenation using metallic catalyst nanoparticles shows that this technique is potentially a key engineering route for graphene nanoribbon fabrication with atomic precision. In this contribution we utilized gas phase prepared cobalt nanoparticles to create etch trenches in multi-layer graphene. Aberration-corrected low voltage high resolution transmission electron microscopy allowed us to directly determine the etch direction of various tracks. The etch channels are shown to be commensurate with the graphite crystal lattice. More importantly, preferred etching along armchair edges was observed, indicating that tailored fabrication of graphene nanostructures with well-defined armchair edges may be possible applying ultrafine catalyst particles. © 2009 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.